Lysotypie Complémentaire de Pseudomonas Aeruginosa - Ferreira, M. O. Santos (2017)
Twenty per cent of Pseudomonas aeruginosa strains isolated in Portugal are non typable with the phage-tvping Lindberg system, but most of them may be typed with the aid of a new phage-tvping method. This complementary scheme of phage-typing is based on the use of 15 new phages from sewage; 39 phage-types were found among a group of the non-tvpable strains isolated in several hospitals in Lisbonne. The relations between the serotypes, the pyocinotypes and the new liysotypes are investigated.